Performance evaluation of grated coconut waste as a bitumen modifier - Wan Noor Hin, Mior Sani; Wan Mohamad Faizrul Hakimi, Wan Ahmad Sofiana; Syarini, Mohd Amin; Mohd Zul Hanif, Mahmud; Rogo, Kabiru Usman; Mohd Hazree, Hashim (Popular Scientist, 2024)
Coconut is extensively utilized in everyday existence, with around 3.18 million tonnes of waste, including grated coconut, being generated. Utilizing grated coconut waste as an ingredient in bitumen could alleviate the challenges encountered by environmental authorities. This study aimed to examine the impact of grated coconut waste on the characteristics of bitumen and evaluate its performance in the bitumen mixture. A mixture of bitumen 60/70 penetration grade and grated coconut waste was created, with varying percentages of 0%, 1%, 2%, and 3%. The mechanical qualities of grated coconut waste as a bitumen modifier were assessed using several tests, including the indirect tensile strength test and the Marshall stability test. The physical and mechanical characteristics of grated coconut waste as a modifier for bitumen were assessed utilizing tests for softening point test and penetration test. Based on this study, the findings for physical properties of penetration and softening point test, the used up until 3% grated coconut waste can give effect to the bitumen stiffness. One of the more significant findings to emerge from this study is that higher stability and tensile strength of 1% grated coconut waste at 10420 N and 271 kPa, respectively. In conclusion, the used of 1% grated coconut waste as a bitumen modifier resulted the positive effect to the physical properties and mechanical properties of the bitumen mixture.